Conflicting Priorities Between Risk Management and Treatment of Schizophrenia in Swiss Forensic Services—A Case Report - Steinau, Sarah; Brackmann, Nathalie; Sternemann, Ulf; Biller-Andorno, Nikola; Habermeyer, Elmar (Frontiers in Psychiatry, 2018)
The Swiss Criminal Code provides measures for mentally-ill offenders focusing on their need for treatment. This may lead to the deprivation of the patient's liberty up to several years. Under certain circumstances the mentally-ill offender can be sentenced to an indefinite incarceration. This case presentation we will describe a forensic psychiatric patient diagnosed with schizophrenia who was ordered an indefinite incarceration in Switzerland after he had been sentenced to 8 years of imprisonment for a deliberate killing. Initial presentation of symptomatology included formal thought disorders and negative symptoms such as affective flattening and alogia. Due to a scarcity of adequate treatment sites in the 90s and lack of scope for risk assessment and management, the patient could only be treated within highly regiment prison environments in the past. There, the patient's treatment concept primarily focused on short-term psychiatric care instead of providing an adequate treatment plan that would have been essential for the patient's improvement of chronic symptoms. This case description aims to present some of the fundamental issues observed in the forensic mental health system, where strong efforts are made to balance risk management and the treatment of severe mental health disorders. We will put the patient's own course of treatment and his progress within the penal system into context with ethical challenges in the forensic and correctional services and will provide potential recommendations for future research in the field of forensic psychiatry.